Semiotika Puisi Tidak Ada New York Hari Ini Karya M Aan Mansyur - Taqwiem, Ahsani (Universitas Islam Negeri Antasari Banajarmasin, 2018)
This study aimed to discover the meaning of Tidak Ada New York Hari Iniâs poetry by M. Aan Mansyur. The approach used in this research is semiotic Michael riffaterre. This research was conducted with several stages, namely; understand the non-existence of expression; conducting heuristic and hermeneutic readings; search for its matrix, model, and variant; as well as finding the hypogram of the text. The results of the discussion can reveal the meaning that contained in the poetry. The discussion also shows poetry Tidak Ada New York Hari Ini is a response from the preceding hypogram.